2020
DOI: 10.1007/s11060-020-03580-y
|View full text |Cite
|
Sign up to set email alerts
|

Repolarization of tumor infiltrating macrophages and increased survival in mouse primary CNS lymphomas after XPO1 and BTK inhibition

Abstract: Background Patients diagnosed with primary central nervous system lymphoma (PCNSL) often face dismal outcomes due to the limited availability of therapeutic options. PCNSL cells frequently have deregulated B-cell receptor (BCR) signaling, but clinical responses to its inhibition using ibrutinib have been brief. In this regard, blocking nuclear export by using selinexor, which covalently binds to XPO1, can also inhibit BCR signaling. Selinexor crosses the blood-brain barrier and was recently shown to have clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 49 publications
(98 reference statements)
0
17
0
Order By: Relevance
“…This finding might provide a preclinical rationale for this two-novel-drug strategy for PCNSL. 100 Chidamide, an oral subtype-selective histone deacetylase inhibitor (HDACI), has been approved by China FDA for the treatment of r/r peripheral T-cell lymphoma (PTCL). 101 A recent study reported that chidamide could significantly upregulate the expression of CD20 on the surface of DLBCL cell lines; thus, it could synergize with rituximab to inhibit tumor growth of DLBCL.…”
Section: Other Novel Therapiesmentioning
confidence: 99%
“…This finding might provide a preclinical rationale for this two-novel-drug strategy for PCNSL. 100 Chidamide, an oral subtype-selective histone deacetylase inhibitor (HDACI), has been approved by China FDA for the treatment of r/r peripheral T-cell lymphoma (PTCL). 101 A recent study reported that chidamide could significantly upregulate the expression of CD20 on the surface of DLBCL cell lines; thus, it could synergize with rituximab to inhibit tumor growth of DLBCL.…”
Section: Other Novel Therapiesmentioning
confidence: 99%
“…In particular, BTK is overexpressed in TAMs a n d M D S C s , w h i c h r e g u l a t e t u m o r p r o g r e s s i o n , immunosuppression and angiogenesis (71,84,85). Ibrutinib treatment, Btk deficiency or siRNA-mediated knockdown of BTK shifts macrophage polarization from tumor-promoting M2-like macrophages toward inflammatory M1-like and diminishes PD-1 and SIRPa expression on macrophages (24,77,86,87). Ibrutinib treatment also inhibits MDSC generation, induces MDSC differentiation to mature DCs, and impairs IDO expression and NO production in MDSCs, resulting in reduced MDSC-mediated immunosuppression and increased CD8 T cell proliferation, infiltration and effector function in the TME (71,80,84,88).…”
Section: Hematological Malignancies Of Myeloid Cells and T Cellsmentioning
confidence: 99%
“…By using orthotopic xenograft models that were established by injecting lymphoma cells into the brain parenchyma of athymic mice, Jimeńez et al demonstrated that selinexor in combination with ibrutinib could effectively suppress tumor growth and prolong the survival of CNS lymphoma mice (35). Tumor cells in their brains were accompanied by tumorassociated macrophages (TAMs) and T cells.…”
Section: Btk Inhibitormentioning
confidence: 99%